PADRE ANTÔNIO VIEIRA E A ECONOMIA PORTUGUESA NA ÉPOCA DA RESTAURAÇÃO (Revista de História Regional, 2007)
The 17th century was a period of intense conflictbetween Portuguese and Spain, due to the end of the IberianUnion, in the year 1640. In this context, we can stress thepersonality of Father Antonio Vieira, who due to hisrelationship with D. João IV presents a series of economicprojects to be implanted in America. Among those that weresuccessful, we can point out the Implantation of the Company of Western Commerce that begins its activities in 1647. Apredominant factor in Vieiras speech is the need to use theJewish money for the execution of his projects; for the Jesuitthis would be the only way for Portugal to win its war againstSpain and balance its accounts. Another important factorand conflict generator is Vieiras defense of the idea thateveryone, including the nobles, should pay tribute to theCrown. Starting form these conflicts, I intend to demonstratehow Father Antonio Vieira understood the PortugueseEconomy at the time to the Restoration, highlighting theactions that had, or could have, influence in the PortugueseAmerica, understanding the Jesuit as a representative of amercantile thought that would be in conflict with otherdeveloping economic models.